EFFECTS OF NO-TILLAGE AND CROPPING SEQUENCE ON POPULATION DENSITIES OF SOME PLANT-PARASITIC NEMATODES - AMOSU, DR. J. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Population densities of Pratylenchus brachyurus and Helicotylenchus pseudorobustus were studied under two no-tillage and conventional tillage methods and under four cropping sequences over a period of two years. Tillage methods and cropping sequences resulted in significant differences in the nematode populations. The densities of P. brachyurus and H. pseudorobustus were highest in the no-tillage plots but lowest under the conventional tillage. The greatest populations of P. brachyurus and H. pseudobustus occurred under continuous maize-maize and rice-rice cropping sequences and were lowest under maize-cowpea cropping sequences.